A new reporting approach for journalistic impact: Bringing together investigative reporting and solutions journalism. (June 2019) - Walth, Brent; Dahmen, Nicole Smith; Thier, Kathryn
Investigative reporting identifies social problems and names people in power who should be held accountable. Solutions journalism is an evidence-based reporting approach that covers credible responses to social problems. To consider these reporting approaches in tandem, this research uses a quantitative content analysis to examine both investigative and solutions reporting in an effort to determine to what extent a combined reporting approach of these two genres may already exist in journalistic practice.